Cover Feature: Convenient Unsymmetrical Disulfane Synthesis: Basic Zeolite‐Catalyzed Thiol‐Disulfane Exchange Reaction (ChemCatChem 22/2021). Issue 22 (28th October 2021) - Yamamoto, Eiji; Kawai, Yasutaka; Takakura, Kei; Kimura, Moemi; Murayama, Haruno; Matsueda, Hironobu; Otsuki, Shujiro; Sakata, Hiroshi; Tokunaga, Makoto
Abstract : The Cover Feature shows cats working as MS‐13X CATalysts and transforming thiols and symmetric disulfanes into the valuable unsymmetrical disulfane, one after another. In their Communication, E. Yamamoto et al. described a basic zeolite‐catalyzed thiol–disulfane exchange reaction for accessing the unsymmetrical disulfanes in a simple and user‐friendly manner using MS‐13X, which is one of the commercially available and cheap molecular sieves, as a basic zeolite catalyst. The reactions were generally carried out in EtOH solvent at room temperature under air, and provide various unsymmetrical disulfanes in good to high yields. Preliminary mechanistic investigations indicated that this reaction involves base‐catalyzed SN2 ‐like processes assisted by hydrogen bonding interactions. More information can be found in the Communication by E. Yamamoto et al.